2020
DOI: 10.1016/j.dyepig.2020.108195
|View full text |Cite
|
Sign up to set email alerts
|

The 2-isocyanoazulene-gold(I) fragment as a versatile element for organometallic dyes and liquid crystals

Abstract: This manuscript reports the synthesis and liquid crystal behavior of isocyanoazulene gold(I) complexes [AuX(CN-Az)] (Az = azulene; X = halide, perhalophenyl or alkynyl) and [µ-4,4'-C6F4C6F4{Au(CN-Az)}2]. The comparison of the X-ray structures of homologous compounds, reveals that the introduction of a long substituent in the system produces a loss of molecular planarity that induces a decrease in the melting temperatures. The free 2isocyanoazulene is not a liquid crystal itself, but its gold complexes bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…In addition, single molecules and nanostructures of 2-isocyano-1,3-di- tert -butoxycarbonylazulene adsorbed on Au(111), where the 2-isocyanoazulenic moieties are decoupled from the gold surface by bulky tert -butoxycarbonyl substituents, have been recently shown to be amenable to controlled manipulations by Scanning Tunneling Microscopy (STM) methods [ 23 ]. Redox-active complexes of ruthenium(II) tetraphenylporphyrin, featuring coordinated 2-isocyanoazulene [ 24 ], and liquid crystals based on the 2-isocyanoazulene complexes of gold(I) [ 25 ] have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, single molecules and nanostructures of 2-isocyano-1,3-di- tert -butoxycarbonylazulene adsorbed on Au(111), where the 2-isocyanoazulenic moieties are decoupled from the gold surface by bulky tert -butoxycarbonyl substituents, have been recently shown to be amenable to controlled manipulations by Scanning Tunneling Microscopy (STM) methods [ 23 ]. Redox-active complexes of ruthenium(II) tetraphenylporphyrin, featuring coordinated 2-isocyanoazulene [ 24 ], and liquid crystals based on the 2-isocyanoazulene complexes of gold(I) [ 25 ] have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…18 They also showed that the herringbone pattern was conserved in the crystallized film and fabricated potent organic field effect transistors (OFETs) with great application potential. [19][20][21][22][23] Although there have been several reports on azulene-based liquid crystals [24][25][26][27][28] and OFETs (Fig. 1(c) and (d)), [29][30][31][32][33][34][35][36][37] the combination of the unique properties of azulene Az and the strong templating effect of the SmE phase remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several reports on azulene-based liquid crystals 24–28 and OFETs (Fig. 1(c) and (d)), 29–37 the combination of the unique properties of azulene Az and the strong templating effect of the SmE phase remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new ligands with increased steric bulk and chelating functional groups ,,,, have been developed to generate new molecular architectures and tune optical properties and catalytic activity. Notably, isocyanoarenes are also known to facilitate electronic communication between metal centers, a property that has been expanded recently in the development of redox-active azulene- and ferrocene-derived isocyano ligands (Chart B) …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electronic properties can also change in response to external stimuli such as temperature, mechanical stress, ,− ,,, irradiation, or the presence of solvent vapors . Only recently, liquid crystalline isocyano–gold­(I) complexes have also been reported (Chart B) …”
Section: Introductionmentioning
confidence: 99%